Implementasi falah dalam ekonomi Islam melalui kesadaran petani sebagai homo Islamicus melaksanakan pembayaran zakat pertanian - Marlya Fatira AK; Muhammad Yasir Nasution; Sugianto Sugianto (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2022)
This article describes the concept of al Ujrah in Islam, which is appropriate as a reference for problems faced by companies or entrepreneurs when experiencing economic difficulties, especially learning from the experience of financial difficulties when faced with the issue of the Covid-19 pandemic 2.5 years ago. As well as the conditions in 2023 presented by the Indonesian and world economies will experience a recession or economic difficulties, so 2023 will be a year full of challenges and struggles for companies in terms of the policy of retaining employees with wages that have been stipulated in work contracts or wage adjustments by making new contracts. The purpose of this research, of course, is to provide accurate and correct references to become a reference for creating policies that are fair for employees as well as safe for companies or employers. This research is a research with a literature study. The data source used is the primary data source. Data collection techniques with literature studies and documentation. The analysis technique was carried out using the meta-analysis-aggregation method, selecting this data analysis to elaborate themes on zakat problems, then forming an analysis framework (conceptual framework), and finally formulating a synthesis by summarizing the various research results or summarizing. The results of the study show that Al Ujrah (wages) are payments or rewards, which can be in the form of goods, money, or other types of assets. Wages are given as an achievement for the results of business or services that have been provided by individuals. Payment of wages (al-ujrah) is carried out based on a work contract (contract), so adjustments to the mechanism and its implementation must also be carried out by deliberation and agreement between the workers and the employer, reflecting fairness and mutual understanding.